Intestinal alkaline phosphatase targets the gut barrier to prevent aging - Kühn, Florian (JCI Insight, 2020)
Gut barrier dysfunction and gut-derived chronic inflammation play crucial roles in human aging. The gut brush border enzyme intestinal alkaline phosphatase (IAP) functions to inhibit inflammatory mediators and also appears to be an important positive regulator of gut barrier function and microbial homeostasis. We hypothesized that this enzyme could play a critical role in regulating the aging process. We tested the role of several IAP functions for prevention of age-dependent alterations in intestinal homeostasis by employing different loss-of-function and supplementation approaches. In mice, there is an age-related increase in gut permeability that is accompanied by increases in gut-derived portal venous and systemic inflammation. All these phenotypes were significantly more pronounced in IAP-deficient animals. Oral IAP supplementation significantly decreased age-related gut permeability and gut-derived systemic inflammation, resulted in less frailty, and extended lifespan. Furthermore, IAP supplementation was associated with preserving the homeostasis of gut microbiota during aging. These effects of IAP were also evident in a second model system, Drosophilae melanogaster. IAP appears to preserve intestinal homeostasis in aging by targeting crucial intestinal alterations, including gut barrier dysfunction, dysbiosis, and endotoxemia. Oral IAP supplementation may represent a novel therapy to counteract the chronic inflammatory state leading to frailty and age-related diseases in humans.